Fetal Alcohol Syndrome: Nursing assistance in the identification, prevention and treatment processes (Research, Society and Development, 2020)
Alcohol consumption permeates humanity in an extremely important way. During pregnancy, drinking alcohol exposes the fetus to profound risks. As a result, Fetal Alcohol Syndrome (APS) affects the fetal central nervous system, which is usually born with low weight, short stature and microcephaly. Objective: To analyze the scientific evidence that points to Nursing Care for children with APS and their family, as well as the possibilities for identification, prevention and treatment. Methodology: This is an Integrative Literature Review with a qualitative approach and descriptive content. The Virtual Health Library was used in June-July 2020, in which it was possible to take advantage of the integration of different databases from the descriptors Pregnant Women, Fetal Alcohol Spectrum Disorder, Nursing and Child Development through the AND connective. At the end of the selection, disposal and reading processes, 7 works were selected. Results: The use of alcohol in the prenatal and postnatal periods results in perceptions and behavior on the part of pregnant women and nurses. Although several problems accompany this complex syndrome, it was identified that the Nursing Process can assist children and their families in different aspects of care in the face of APS. Conclusion: There is a gap between the professional nurse and the pregnant woman. Now because there is no sharing of doubts about alcoholism and its difficult identification, now because there is little interest in enhancing strategic knowledge to deal with situations. Such factors have little influence on the harmful effects of alcohol on the body.